2018
DOI: 10.12659/ajcr.909523
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Metastasis of Thyroid Carcinoma: A Case Report

Abstract: Patient: Male, 58Final Diagnosis: Pituitary metastais from thyroid carcinomaSymptoms: Visual acuity worseningMedication: —Clinical Procedure: NeurosurgerySpecialty: Endocrinology and MetabolicObjective:Rare diseaseBackground:Pituitary metastasis of thyroid carcinoma is a rare entity. Differential diagnosis with other lesions in the sellar/parasellar region, through clinical, histopathological, immunohistochemical, and imaging is challenging but essential for adequate treatment.Case Report:This case report desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Rarely does a DTC metastasise to the pituitary. There are fewer than 20 published cases of a pituitary metastasis arising from an FTC and only one report of a pituitary metastasis from HCC was found in our literature search 3 4. We describe another case of a pituitary metastasis from HCC.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Rarely does a DTC metastasise to the pituitary. There are fewer than 20 published cases of a pituitary metastasis arising from an FTC and only one report of a pituitary metastasis from HCC was found in our literature search 3 4. We describe another case of a pituitary metastasis from HCC.…”
Section: Introductionmentioning
confidence: 82%
“…HCCs are a group of heterogeneous malignant tumours that exhibit diverse biological features and represent less than 5% of DTC 3. HCC is regarded as an oncocytic variant of FTC by the WHO 5.…”
Section: Discussionmentioning
confidence: 99%
“…We performed research in PubMed, looking for other cases of pituitary metastases and we found 107 cases between case series and single case reports ( 11 30 -33). We found only 7 cases of pituitary metastasis originating from gastroenteric tract ( 12 , 25 , 29 , 31 , 32 ) and no cases of pituitary metastasis from gastro-esophageal junction adenocarcinoma ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunochemistry was suggestive of ATC with thyroid transcription factor 1 (TTF-1), cytokeratin, Pax8, and C53 positive while calcitonin and thyroglobulin were negative. Immunohistochemistry can complement histopathology for accurate diagnosis of uncommon tumors [12]. Radiation therapy is a well-tolerated treatment approach with or without surgery or chemotherapy in the context of loco-regional control for patients with ATC [13].…”
Section: Discussionmentioning
confidence: 99%